Penilaian Kinerja Keuangan PT Bank Muamalat Indonesia, Tbk dengan Metode Economic Value Added - Budi Gautama Siregar; Muhammad Salman; Aswadi Lubis (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to analyze the financial performance of PT. Bank Muamalat Indonesia Tbk uses the Economic Value Added (EVA) method in the period 2018 to 2022. EVA is one of the methods used to measure the extent to which a company can create economic added value by comparing the net profit obtained by the company with the cost of capital used. The results of the study show that the financial performance of PT. Bank Muamalat Indonesia Tbk experienced significant fluctuations during this period. In 2019, EVA experienced a sharp decline of 68.37%, which was caused by an increase in equity, an increase in tax burden, and a decrease in revenue. In 2020, the company managed to turn things around with an increase in EVA of 76.31%, driven by a decrease in equity and tax burden. However, in 2021 and 2022, EVA experienced a decline again, by 64.48% and 38.36%, respectively, due to an increase in tax burden and a decrease in revenue. Despite the fluctuations, EVA still showed a positive number (EVA > 0), which indicates that the company is able to create added value for shareholders. The results of this study found that factors that affect EVA include income, tax burden, and equity structure. It is recommended for companies to pay attention to tax management, optimization of capital structure, and diversification of sources of income. The limitations of this study lie in the limited data coverage of the annual financial statements and the relatively short research period. Further research is recommended to use longer periods and consider external factors that affect the company's performance.